2020
DOI: 10.1111/ajt.15609
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric living donor liver transplantation with large-for-size left lateral segment grafts

Abstract: Usage of “large‐for‐size” left lateral segment (LLS) liver grafts in children with high graft to recipient weight ratio (GRWR) is controversial due to concerns about increased recipient complications. During the study period, 77 pediatric living donor liver transplantations (LDLTs) with LLS grafts were performed. We compared recipients with GRWR ≥2.5% (GR‐High = 50) vs GRWR <2.5% (GR‐Low = 27). Median age was higher in the GR‐Low group (40 vs 8 months, P> .0001). Graft (GR‐High: 98%, 98%, 98% vs GR‐Low: 96%, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 26 publications
(68 reference statements)
3
36
0
Order By: Relevance
“…In a study by Li et al, 252 patients underwent LDLT and were categorized into three Groups by GRWR; the authors concluded that the GRWR in pediatric LDLT is a major risk factor that affects survival and recommended a GRWR between 2% and 4% as the optimal range [ 8 ]. Goldaracena et al reported that pediatric LDLT with grafts having a GRWR ≥ 2.5%, and even >4%, can be performed safely with similar results as graft having a GRWR < 2.5% [ 10 ]. They also observed a higher rate of delayed abdominal wall closure that did not impact on the overall outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Li et al, 252 patients underwent LDLT and were categorized into three Groups by GRWR; the authors concluded that the GRWR in pediatric LDLT is a major risk factor that affects survival and recommended a GRWR between 2% and 4% as the optimal range [ 8 ]. Goldaracena et al reported that pediatric LDLT with grafts having a GRWR ≥ 2.5%, and even >4%, can be performed safely with similar results as graft having a GRWR < 2.5% [ 10 ]. They also observed a higher rate of delayed abdominal wall closure that did not impact on the overall outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatives to left lateral sector in paediatric liver transplantation-a systematic review on monosegmental and reduced grafts and delaying abdominal wall closure (4,5) or surgically altering the LLS and aiming for a primary closure. In 1992, to confront this problem, Strong et al (6) published the first monosegmental pLT, implanting the segment 3 from a DD into a 4-month-old baby (a redo transplant for HAT).…”
Section: Review Articlementioning
confidence: 99%
“…Accordingly, a 5 Kg child receiving a LLS graft, will likely face a GRWR close to 5% (1:1 equivalence between cc and grams). It is well documented that GRWR is a strong predictor of graft survival and the vast majority of reports concur that those grafts exceeding 4% will likely generate a conflict with the abdominal cavity's capacity (4,5,13,(16)(17)(18)(19)(20)(21)25,(36)(37)(38). Hence, some groups advocate for altering the LLS, reducing or converting it into a monosegment.…”
Section: Are the Different Modalities For Surgically Manipulating A Lls Comparable?mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the shortage of size‐matched donors in pLT regularly requires the implantation of LFS grafts from adult donors. This donor‐recipient size discrepancy is one of the most complex and challenging problems for transplant surgeon …”
Section: Introductionmentioning
confidence: 99%